Respuesta :
We are given with RM = SN, TM = TN and we are to prove that RN = SM. The steps that are followed for this proof are as follow:
1. RM = SN , TM = TN Given
2. ∠T = ∠T Reflexive
3. RM + TM = SN + TN Addition Property of Equality
4. RM + TM = RT, SN + TN = ST Betweeness
5. RT = ST Substitution
6. Triangle RTN congruent to Triangle STM SAS
7. RN = SM CPCTE
1. RM = SN , TM = TN Given
2. ∠T = ∠T Reflexive
3. RM + TM = SN + TN Addition Property of Equality
4. RM + TM = RT, SN + TN = ST Betweeness
5. RT = ST Substitution
6. Triangle RTN congruent to Triangle STM SAS
7. RN = SM CPCTE
Answer:
We have to match the following statements to the given proof.
S.No. Proof Statement
------------------------------------------------------------------------------------------------------
1 RM=SN Given
TM=TN
------------------------------------------------------------------------------------------------------
2 ∠T=∠T Reflexive
-------------------------------------------------------------------------------------------------------
3 RM+TM=SN+TN Addition property
of equality
( by using 1)
-----------------------------------------------------------------------------------------------------
4 RM+TM=RT, Betweeness
SN+TN=ST
---------------------------------------------------------------------------------------------------
5 RT=ST Substitution( since using
equation 3 and 4)
-----------------------------------------------------------------------------------------------------
6 ΔRTN≅ΔSTM SAS ( since two sides and
corresponding angle are
equal by 1,2 and 5)
-----------------------------------------------------------------------------------------------------
7 RN=SM CPCTE( Corresponding parts of
congruent triangles are equal)
-----------------------------------------------------------------------------------------------------